Comparing the effectiveness of positive couple therapy group training and integrated behavioral approach on empathy and intimacy of infertile couples - Vahidi Farashah, Mohammad; Shafieabadi, Abdollah; Khodabakhshi Koolaee, Anahita (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to compare the effectiveness of positive couple couple therapy group training and integrated behavioral approach on empathy and intimacy of infertile couples. Methods: The research method was quasi-experimental or pre-test, post-test and follow-up with a control group. The statistical population of the study includes all infertile couples who referred to counseling and treatment centers in Shiraz in 2019, among whom 45 were selected by purposive sampling method and based on the convenience sampling method from the referring couples. Were randomly assigned to three groups of 15 individuals. Christensen et al.’s (2010) behavioral-integrated couple therapy program was performed in 8 sessions of 90 minutes and the positive couple therapy program of Rashid and Seligman (2013) was performed in 8 sessions of 90 minutes weekly but the control group did not receive any intervention. All three groups answered the Juliet and Farrington (2006) empathy questionnaires and Walker and Thompson (1983) marital intimacy questionnaires in pre-test, post-test and follow-up. Data were analyzed using repeated measures analysis of variance using SPSS.22 software. Results: The results showed that both therapies could improve empathy (F= 107.92, P<0.001), and marital intimacy (F= 116.81, P<0.001), but Positive group education had a greater effect on research variables (P<0.01). Conclusion: It can be concluded that group training of positive couple therapy and integrated behavioral approach is effective on empathy and intimacy of infertile couples and can be effective in improving the problems of infertile couples.